The Impact of Extensive Reading Using er-central.com to Promote Reading Habit Among EFL High School Students in East Java: A Qualitative Case Study - Achmad Yusuf; Pratiwi Retnaningdyah; Him’mawan Adi Nugroho (Dinasti Publisher, 2024)
This study aims to investigate the impact of extensive reading program using the website er-central.com to promote reading habit among high school students in East Java. The study employs a qualitative case study where the program has been done in a high school of 17 Agustus 1945 Senior High School which runs the extensive reading using a digital website. The data is given in two ways, the report of students' reading progress on the administrator page and the response to an open-ended questionnaire that asks students’ perception of how the program impacts their reading habits. The 5 examples of students reading progress reports show that students' reading is still in progress where students have the autonomy to choose the texts and do the quiz. The answers to the open-ended questionnaire show that students argued the program impacts their reading habits. It is shown that 60.78% of the respondents agreed that extensive reading encourages them to read and be autonomous. It can be concluded that the extensive reading program encourages the students’ reading habits.